Immediate postpartum modern family planning utilization and associated factors among postpartum women in Gurage Zone, Southern Ethiopia 2022: community-based cross-sectional study - Gudeta, Tolesa Gemeda; Terefe, Ayana Benti; Mengistu, Girma Teferi; Sori, Seboka Abebe (Frontiers in Global Women's Health, 2025)
BackgroundThe period immediately following delivery is crucial for addressing the many requirements women have in terms of reproductive health, including the need for family planning after delivery and for lowering the risks associated with closely spaced pregnancies. However, contraception during the immediate postpartum period has not received enough attention in Ethiopia. Information on the use of modern family planning in the immediate postpartum period is also sparse in this study area. Therefore, the current study aimed to assess the level of immediate postpartum modern family planning utilization and associated factors among mothers who had given birth within the past twelve months in Gurage Zone, Southwest Ethiopia.MethodsThe present study was conducted from May 1 to July 1, 2022, involving 844 mothers who had given birth in the previous year in the Gurage Zone of Southern Ethiopia. A community-based cross-sectional study design was utilized, with participants selected through a multistage sampling method. Data collection was performed via face-to-face interviews using a structured questionnaire. After data entry, which was done using EpiData version 3.1, analysis was carried out using the Statistical Package for Social Science (SPSS) version 26. To investigate the relationships between dependent and independent variables, both binary and multivariable logistic regressions with 95% confidence intervals were applied. In the multivariable logistic regression analysis, variables with P-values below 5% were considered statistically significant.ResultAltogether, a total of 836 postpartum women participated in the current study. The overall prevalence of immediate postpartum modern family planning utilization (IPPFP) was (42.9%) with 95% CI (39.6–46.3%). Attending secondary school [AOR = 1.966(1.028–3.761)], postpartum women from wealthier families [AOR = 2.57 (95% CI: 1.44–4.58)], giving birth in health facility [AOR = 2.06 t (95% CI: 1.26–3.38)], reporting higher women empowerment [AOR = 4.365 (2.436–7.824)], having favorable attitude [AOR = 2.65 (95% CI: 1.86–3.78)], getting counseling during ANC [AOR = 1.93 (95% CI: 1.36–2.76)] and immediate postpartum period [AOR = 2.51 (95% CI: 1.77–3.56)] were significant associated factors of IPPFP utilization.ConclusionThis study concluded that approximately two in five postpartum women utilized immediate postpartum family planning this study area. Socio-economic and informational factors significantly influence the adoption of these methods. To enhance the uptake of immediate postpartum family planning, it is essential to improve the quality of counseling provided during antenatal care visits and at the time of delivery, thereby empowering women with the knowledge needed for informed decision-making. Additionally, efforts to change attitudes toward immediate postpartum family planning through community education and awareness campaigns are vital for increasing acceptance and utilization of these services.